2023
DOI: 10.1002/andp.202300232
|View full text |Cite
|
Sign up to set email alerts
|

Propagation Characteristics of a Partially Coherent Gaussian Schell‐model Array Vortex Beam in the Joint Turbulence Effect of a Jet Engine and Atmosphere

Hassan Nabil,
Adil Balhamri,
Mert Bayraktar
et al.

Abstract: This work investigates the joint effects of jet engine exhaust‐induced turbulence and atmospheric turbulence on the propagation of a partially coherent Gaussian Schell‐model Array (GSMA) vortex beam. Using the two‐process propagation method, analytical formulae are derived for the cross‐spectral density, spectral density, degree of coherence, and beam width of the considered beam. The results show that the considered beam takes different shapes; when the spatial coherence is large, the spectral density of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…One of the most important points is that the effect of turbulence caused by the jet engine on the propagation of the beam, especially over short distances, was also investigated. In the analysis of partially coherent Gaussian Schell-model array vortex beam, it was found that as the propagation distance, topological load, and turbulence power increased, the degree of consistency gradually decreased and turned into a Gaussian profile [4]. A comparison of the power in bucket fluctuations between 4.6 and 2.4 μm wavelengths was made and showed [5] more fluctuations at shorter wavelengths due to increased phase perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important points is that the effect of turbulence caused by the jet engine on the propagation of the beam, especially over short distances, was also investigated. In the analysis of partially coherent Gaussian Schell-model array vortex beam, it was found that as the propagation distance, topological load, and turbulence power increased, the degree of consistency gradually decreased and turned into a Gaussian profile [4]. A comparison of the power in bucket fluctuations between 4.6 and 2.4 μm wavelengths was made and showed [5] more fluctuations at shorter wavelengths due to increased phase perturbations.…”
Section: Introductionmentioning
confidence: 99%